3D Biomimetic matrices to design in vitro stem cell niches - Martins Figueiredo, Lara Isabel (2018)
Tissue engineering (TE) is a rapidly evolving interdisciplinary field that joins together materials science, biomedical engineering and cellular biology, in a quest to reconstruct living tissues upon injury or loss. For this reason TE has the potential to have a large impact in clinical implantations, expanding tissue supply for transplantation therapies. The scaffold is a centrepiece in TE, since it aims to mimic the extracellular matrix (ECM) that is found in natural tissue. Nonetheless, a major constraint in achieving larger constructs has been the lack of means to transport oxygen and waste produced by the cells. The construction of complex structures with an integrated vasculature, with high spatial resolution, is now a reality that opens the door for more complex and larger engineered tissues and organs. This thesis presents the results of a study on the impact on oxygen diffusion and cell viability in stem cell seeded constructs, after biomaterial (hydrogel) mechanical reinforcement with a laponite clay, considered to be of great potential for regenerative medicine. The impact on oxygen and nutrient diffusion and cell viability in stem cell seeded constructs after hydrogel mechanical reinforcement through polymer concentration is also presented and discussed. The impact on oxygen diffusion and cell viability after the creation of a microchannel network inside stem cell constructs, through a bioprinting technique, was quantified and constitutes the last part of the present work.